1969
DOI: 10.2466/pr0.1969.25.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Role of Memory in Divergent Thinking

Abstract: Tests involving word span, memory for verbal details, memory for visual details, and the Minnesota Tests of Creative Thinking (MTCT) were administered to 63 Ss in grades 4, 5, and 6. IQs were obtained from school records. Only 1 of 8 correlations between IQ and divergent thinking (DT) scores was significant, but 11 of 48 correlations between memory and DT were significant. In stepwise multiple correlation of the memory scores on each DT score, 17 of 19 predictor variables in reduced sets were memory scores. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In such cases, participants may adopt alternative strategies for generating responses, such as deriving words associated with episodic memories evoked by the cue. This episodic memory strategy, we predicted, would be most effective when the cue words are imageable (i.e., high in imagery) and can evoke recollections or other episodic‐like processes more easily than words that are not as imageable (Paivio et al,1968; Richardson,1992; Moulton and Kosslyn,2009). Control participants could take advantage of the evoked episodic memory by quickly accessing a memory or simulated scene and produce a word associated with it.…”
Section: Discussionmentioning
confidence: 92%
“…In such cases, participants may adopt alternative strategies for generating responses, such as deriving words associated with episodic memories evoked by the cue. This episodic memory strategy, we predicted, would be most effective when the cue words are imageable (i.e., high in imagery) and can evoke recollections or other episodic‐like processes more easily than words that are not as imageable (Paivio et al,1968; Richardson,1992; Moulton and Kosslyn,2009). Control participants could take advantage of the evoked episodic memory by quickly accessing a memory or simulated scene and produce a word associated with it.…”
Section: Discussionmentioning
confidence: 92%
“…One examination of the relationships between intelligence, cre ativity, and memory was carried out by Pollert,(1969)o He hypothesized that memory was importanc to creativityJ and his results supported this hypotheSiS, with one predictable exception: two rote memory tasks showed no relation to non-verbal creativity and only a very small rela tion to verbal creativity and intelligence. Rote memory is known to b9 quite independent of intelligence tests (Cronbach, 1910).…”
Section: Memory and Setsmentioning
confidence: 71%
“…Some indivi.duals seem to be significantly more efficient than others at non :rote memory (learning and 'recall of meaningful infonr..ation), and this variable efficiency is constantly fotmd to be correlated tQ intelli gence-te~rt; scores (Matarazzo, 1972;Pollert, 1969). The source of indiv idual differences in non-rote memory is difficult to ascertain.…”
Section: The Problem Of Higher Mental Processesmentioning
confidence: 99%
“…Moreover, teaching activities have been found to boost students' creative thinking (e.g., Neethling, 2000;Torrance, 1988). Generally, studies on creativity have identified the various factors that should be encouraged and improved by teachers; these include cognitive factors (Cropley, 1992;Pollert, Feldhusen, Van Mondfrans, & Treffinger, 1969), motivation factors (Beghetto, 2005;Cropley, 1997;Torrance, 1992), personality factors (Amabile, 1996;Beghetto, 2005;Cannatella, 2004;Gardner, 1988;Von Eschenbach & Noland, 1981), and social factors (Cropley, 1992, Torrance, 1992.…”
Section: On the Factors That Enhance Creativitymentioning
confidence: 99%